2020
DOI: 10.9758/cpn.2020.18.3.423
|View full text |Cite
|
Sign up to set email alerts
|

Agomelatine for the Treatment of Generalized Anxiety Disorder: A Meta-Analysis

Abstract: Objective Despite multiple drugs available, a large proportion of patients with generalized anxiety disorder (GAD) do not show adequate response and remission. Thus, additional novel pharmacological agents are needed to increase treatment option for GAD. We aimed to investigate efficacy and safety of agomelatine in the treatment of GAD by conducting a meta-analysis. Methods An extensive search of multiple databases and clinical trial registries were conducted. Mean chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…In the largest meta-analyses for anxiety disorders, pharmacotherapies achieved SMDs in comparison to placebo between 0.33 and 0.45 53,56,64 (see Figure 2). Overall, effect sizes for pharmacotherapy were between 0.01 and 0.56, with the majority of effect sizes being small 53,[55][56][57][58][59][60][61][62][63][64]66,67,69,70 (see supplementary information). RR ranged between 1.20 and 4.03, with most values being small, one medium (monoamine oxidase inhibitors), and one large (benzodiazepines, RR=4.03) 69 .…”
Section: Anxiety Disordersmentioning
confidence: 99%
“…In the largest meta-analyses for anxiety disorders, pharmacotherapies achieved SMDs in comparison to placebo between 0.33 and 0.45 53,56,64 (see Figure 2). Overall, effect sizes for pharmacotherapy were between 0.01 and 0.56, with the majority of effect sizes being small 53,[55][56][57][58][59][60][61][62][63][64]66,67,69,70 (see supplementary information). RR ranged between 1.20 and 4.03, with most values being small, one medium (monoamine oxidase inhibitors), and one large (benzodiazepines, RR=4.03) 69 .…”
Section: Anxiety Disordersmentioning
confidence: 99%
“…Although studies confirmed its anti-suicidal effects in patients with MDSI, but whether or not the anti-suicidal effects are rapid is still obscure. In terms of understanding efficacy and safety of a new drug, meta-analysis is important because it can overcome limitation of small sample sizes, increase statistical power of group comparisons, enhance generalizability of DB-RCTs, and quantify inconsistencies of DB-RCTs [ 22 , 23 ]. An initial meta-analysis for intranasal esketamine showed that significant superiority of intranasal esketamine over placebo with regard to response and remission in patients with MDD were noted as early as two hours [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, high doses MT may have a beneficial role in patients treated for SARS-CoV-2-induced pneumonia, in terms of reduced time to clinical improvement and even possible lower mortality rates [ 271 ]. Given its inherent anxiolytic and antidepressant properties [ [272] , [273] , [274] ], agomelatine could be a useful medicine to consider in COVID-19 related mood and anxiety disorders.…”
Section: Adjunctive Psychotropic Treatments During Sars-cov-2 Infectimentioning
confidence: 99%